Different strategies of use of commercial effective microorganisms in the rearing of white shrimp Litopenaeus vannamei in biofloc system (Acta Scientiarum. Biological Sciences, 2024)
An experiment was conducted for eight weeks, in a BFT system, to test different strategies for using effective microorganisms (AEM) in shrimp rearing. For that, five different treatments were tested. The treatments tested were: Control (commercial feed only), AEM in the feed (addition of AEM in the commercial feed), AEM in the water (addition of AEM directly in the rearing water), AEM in the feed and in the water (addition of AEM in the feed simultaneously with the addition of AEM in the water) and MA in the feed (addition of the microbiological activator-MA in the commercial feed, without adding microorganisms to the feed and water). The use of AEM or MA, although it did not affect the growth of the animals, stimulated the digestive process of the animals, allowing the required absorption of nutrients with a smaller intestinal area. Associated with this, the presence of AME or MA stimulated the immunological parameters of the animals and reduced the presence of Vibrio in the gut of the shrimp. The association of these factors meant that the survival of the animals that received the additives in the diet was substantially higher than the animals that did not receive the additives. The AEM supplementation strategies did not differ among themselves, and the producer could opt for the strategy of lower cost and/or less complexity of use, according to each specific case.